8 Del. Laws 208 (1841) - (:unkn) unknown (My University, 1832)
A Supplement to an Act to Prevent the Use of Firearms by Free Negroes and Free Mulattoes, and for Other Purposes, ch. 176, § 1: Prohibited "free negroes and free mulattoes" from having, owning, keeping, or possessing any gun, pistol, sword, or warlike instrument without permission of five or more citizens of the neighborhood.
Keywords: ENSLAVED PERSONS & OTHER MINORITIES